Simple Synthesis of CuInS2/ZnS Core/Shell Quantum Dots for White Light-Emitting Diodes - Li, Huimin; Jiang, Xiaohong; Wang, Anzhen; Chu, Xiaotian; Du, Zuliang (Frontiers in Chemistry, 2020)
In this study, the CuInS2/ZnS core/shell quantum dots (QDs) were prepared via simple and environmentally friendly solvothermal synthesis and were used as phosphors for white lightemitting diodes (WLEDs). The surface defect of the CuInS2 core QDs were passivated by the ZnS shell by forming CuInS2/ZnS core/shell QDs. By adjusting the Cu/In ratio and the nucleation temperature, the photoluminescence (PL) peak of the CuInS2 QDs was tunable in a range of 651-775 nm. After coating the ZnS layer and modifying oleic acid ligands, the PL quantum yield increased to 85.06%. The CuInS2/ZnS QDs powder thermal stability results showed that the PL intensity of the QDs remained 91% at 100 °C for 10 mins. With high color rendering index values (CRI, 90) and correlated color temperature of 4360 K for the efficient WLEDs were fabricated using CuInS2/ZnS QDs and (Ba,Sr) 2 SiO4 :Eu2+ as colour converters in combination with blue GaN light-emitting diodes chip.